2019
DOI: 10.1371/journal.pone.0226939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimentally induced fatigue on healthy older adults’ gait: A systematic review

Abstract: IntroductionWhile fatigue is ubiquitous in old age and visibly interferes with mobility, studies have not yet examined the effects of self-reported fatigue on healthy older adults’ gait. As a model that simulates this daily phenomenon, we systematically reviewed eleven studies that compared the effects of experimentally induced muscle and mental performance fatigability on gait kinematics, variability, kinetics, and muscle activity in healthy older adults.MethodsWe searched for studies in databases (PubMed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Repetitive sit-to-stand (rSTS) is a model to induce muscle fatigability in lower extremity muscles and probe gait adaptability 37 . Following bouts of rSTS, maximal voluntary force, the associated surface electromyographic (EMG) activity, and median frequency of muscles involved in gait can decrease up to 18% 35,38 .…”
mentioning
confidence: 99%
“…Repetitive sit-to-stand (rSTS) is a model to induce muscle fatigability in lower extremity muscles and probe gait adaptability 37 . Following bouts of rSTS, maximal voluntary force, the associated surface electromyographic (EMG) activity, and median frequency of muscles involved in gait can decrease up to 18% 35,38 .…”
mentioning
confidence: 99%
“…In accordance with our first hypothesis, we observed increased postural sway (CoP d ), sway velocity (CoP v ), and sway variability (CV CoP d and CV CoP v ) during quite bipedal standing on a wobble board after performing a modified sit-to-stand task till exhaustion in healthy young adults. These results indicate the negative effects of PF on balance performance, although Santos et al (2019) point out that fatigue-related changes after multi joint exercise are the result of combined physiological and mental fatiguing effects.…”
Section: Discussionmentioning
confidence: 73%
“…Although some researchers suggested that experimentally induced muscle fatigue affects the generation of mechanical work and power in lower-limb joints even during gait [69,70], a previous study found no effects of hundreds of sit-to-stand trials on knee MVIC in healthy younger and older adults [71]. A previous review discussed that muscle fatigue induced by repetitive single-joint muscle contractions such as knee extension-flexion is most probably due to a localized force impairment, while when a multi-joint fatiguing protocol is used (e.g., sit-to-stand task, 6-min walk test), any adaptation in gait after the task is the result of a combined physiological and cognitive effect [72].…”
Section: Introductionmentioning
confidence: 99%